(untitled) (Acta Scientiarum. Agronomy, 2025)
Crossing between sexual artificial tetraploids of Urochloa ruziziensis and apomictic polyploids of Urochloa decumbens, and Urochloa brizantha is a breeding strategy. Crosses are carried out without prior emasculation of the plants; therefore, confirmation of hybridization and identification of pollen donors require reliable techniques such as microsatellite markers. Information on the reproductive mode, chromosome number, and genome size is also important. The aims of this study were (i) to identify the male parents and mode of reproduction of the three hybrids using molecular markers, (ii) to define the chromosome number and ribosomal DNA (rDNA) sites using fluorescent in situ hybridization (FISH), and (iii) to estimate genome size using flow cytometry. The simple sequence repeats (SSR) markers identified U. brizantha cv. Marandu, U. brizantha genotype 2 and U. brizantha cv. Xaraés as the male parents of hybrids 1F/21, 7F/153, and 10F/v5, respectively. The 1F/21 hybrid was aneuploid (2n = 36+1, 2C = 3.61 pg), whereas the 7F/153 (2n = 40, 2C = 3.79 pg) and 10F/v5 (2n = 41, 2C = 3.88 pg) hybrids resulted from interploid crosses involving U. brizantha (2n = 5x = 45). The p779/p780 apospory marker was not amplified in the hybrids, indicating sexual reproduction. The number of rDNA sites shows a dynamic behavior and inheritance of these sequences, while the position of the sites on the chromosomes is conserved within the ‘brizantha’ complex. Identifying interploid hybrids provides new perspectives for Urochloa breeding, with the possibility of exploring the genetic variability of other apomictic polyploids. These results are promising in terms of inferences and highlight the need for further studies on interploid hybridization in Urochloa.